Mastering Microsoft SQL server 2005 Express edition - Gunderloy, Mike (Wiley, 2006)
Whether you're a systems administrator, database application developer, or IT consultant, you'll quickly ratchet up your knowledge of Microsoft SQL Server 2005 with this thorough and comprehensive guide. Light on theory and heavy on practicality, it cuts to the chase with real-world examples of large-scale business applications, an entire chapter on troubleshooting, and crucial information on SQL Server 2005's enhanced connectivity. For new users of Microsoft SQL Server, this book takes you quickly, but systematically, through the introductory topics.